Comparative Analysis of Determination Palangka Raya Religious Court and Kasongan Religious Court Regarding Polygamy Marriage Isbat - Amanour Hakim; Sadiani (Mir'ah: Family Law and Legal Culture, 2024)
This research is motivated by the existence of different determinations in the case of Isbat Nikah Polygamy between the Palangka Raya Religious Court and the Kasongan Religious Court. The Palangka Raya Religious Court granted Isbat Nikah while the Kasongan Religious Court refused. The focus of this research is to find out the differences in legal considerations in the determination of the Palangka Raya Religious Court and the Kasongan Religious Court in the application for Isbat Nikah Polygamy and what is the correct determination between the two Religious Courts in allowing or prohibiting the occurrence of Isbat Nikah Polygamy. This research is a type of normative research that examines the legal considerations of the Palangka Raya Religious Court and the Kasongan Religious Court through a statutory approach. The results of this study indicate that there are differences in legal considerations. The Palangka Raya City Religious Court granted the reason that the Applicant was not in accordance with SEMA No. 3/2018 concerning the application for Isbat nikah Polygamy on the basis of nikah siri, which was deemed inappropriate on the grounds of overriding the principle of lex superior derogat legi inferior which prioritizes the Compilation of Islamic Law over the Marriage Law which has a higher position. As for the legal considerations of the Kasongan Religious Court which stated that it refused on the grounds that Applicant I was still bound by marriage, there was no divorce and did not obtain permission for polygamy from the court in accordance with the principle of lex superior derogat legi inferior.